People with tobacco use disorder exhibit more prefrontal activity during preparatory control but reduced anterior cingulate activity during reactive control. (27th February 2022) - Kalhan, Shivam; Chen, Li Peng Evelyn; Garrido, Marta I.; Hester, Robert
Abstract: Reduced inhibitory control and a hypersensitivity to reward are key deficits in drug dependents; however, they tend to be studied in isolation. Here, we seek to understand the neural processes underlying control over reward and how this is different in people with a tobacco use disorder (pTUD). A novel variant of the monetary incentive delay task was performed by pTUD ( n = 20) and non‐smokers ( n = 20), where we added a stop‐signal component such that participants had to inhibit prepotent responses to earn a larger monetary reward. Brain activity was recorded using functional magnetic resonance imaging (fMRI). We estimated stop signal reaction times (SSRTs), an indicator of impulsivity, and correlated these with brain activity. Inhibitory accuracy scores did not differ between the control group and pTUD. However, pTUD had slower SSRTs, suggesting that they may find it harder to inhibit responses. Brain data revealed that pTUD had greater preparatory control activity in the middle frontal gyrus and inferior frontal gyrus prior to successful inhibitions over reward. In contrast, non‐smokers had greater reactive control associated with more activity in the anterior cingulate cortex during these successful inhibitions. SSRT–brain activity correlations revealed that pTUD engaged more control‐related prefrontal brain regions when SSRTs are slower. Overall, while the inhibition accuracy scores were similar between groups, differential neural processes and strategies were used to successfully inhibit a prepotent response. The findings suggest that increasing preparatory control in pTUD may be one possible treatment target in order to increase inhibitory control over reward. Abstract : Prior to successful inhibitions (preparatory control) over rewards, people with a tobacco‐use disorder (pTUD) show greater activity in the prefrontal cortex (inferior frontal gyrus [IFG] and middle frontal gyrus [MFG]). However, during successful inhibitions (reactive control), the control group shows greater activity in the anterior cingulate cortex (ACC). Therefore, both groups use different strategies to successfully inhibit responses in order to attain a larger later reward.